Virtual screening on an α‐helix to β‐strand switchable region of the FGFR2 extracellular domain revealed positive and negative modulators. Issue 11 (30th August 2014) - Diaz, Constantino; Corentin, Herbert; Thierry, Vermat; Chantal, Alcouffe; Tanguy, Bozec; David, Sibrac; Jean‐Marc, Herbert; Pascual, Ferrara; Françoise, Bono; Edgardo, Ferran
ABSTRACT The secondary structure of some protein segments may vary between α‐helix and β‐strand. To predict these switchable segments, we have developed an algorithm, Switch‐P, based solely on the protein sequence. This algorithm was used on the extracellular parts of FGF receptors. For FGFR2, it predicted that β4 and β5 strands of the third Ig‐like domain were highly switchable. These two strands possess a high number of somatic mutations associated with cancer. Analysis of PDB structures of FGF receptors confirmed the switchability prediction for β5. We thus evaluated if compound‐driven α‐helix/β‐strand switching of β5 could modulate FGFR2 signaling. We performed the virtual screening of a library containing 1.4 million of chemical compounds with two models of the third Ig‐like domain of FGFR2 showing different secondary structures for β5, and we selected 32 compounds. Experimental testing using proliferation assays with FGF7‐stimulated SNU‐16 cells and a FGFR2‐dependent Erk1/2 phosphorylation assay with FGFR2‐transfected L6 cells, revealed activators and inhibitors of FGFR2. Our method for the identification of switchable proteinic regions, associated with our virtual screening approach, provides an opportunity to discover new generation of drugs with under‐explored mechanism of action. Proteins 2014; 82:2982–2997. © 2014 Wiley Periodicals, Inc.